MyIMCA: An initiative towards Malaysia’s Marine 30×30 - Affendi, Yang Amri; Poh Leem, Choo; Shantini, Guna Rajan; Aazani, Mujahid; Cindy, Peter (2025)
The idea of 30×30 is a global initiative at the government level to designate 30% of a country’s terrestrial and marine habitats by 2030. As of November 2022, approximately 5.6% of Malaysia’s coastal and marine waters are legally protected. To support and prepare Malaysia in joining the 30×30 conservation initiative, local experts with extensive knowledge and understanding of Malaysia’s coastal and marine biodiversity gathered and brainstormed in three workshops (March 2020, June 2021 and September 2021). These workshops were organised by the Malaysian Society of Marine Sciences (MSMS) and World Wide Fund for Nature Malaysia (WWF-MY) to consolidate, map, and document important coastal and marine areas in Malaysia which included habitats such as coral reefs, seagrass meadows and mangrove forests. The guiding tool was the Ecologically or Biologically Significant Marine Areas (EBSA) criteria of the Convention of Biological Diversity (CBD). Twenty-four sites were collaboratively identified as being important biodiversity areas according to the seven EBSA criteria, stretching from the Straits of Malacca to the Sulu-Sulawesi Sea. The term, ‘Malaysian Important Marine and Coastal Areas (MyIMCA)’, was coined to refer to these sites and are proposed to be protected. If so, these MyIMCA sites will help realise our ambitious 30×30 target.